The climate and trade nexus in Africa: Climate change and the transformation of African trade - Jodie Keane; Max Mendez-Parra; Laetitia Pettinotti; Lily Sommer (Overseas Development Institute (ODI), 2021)
This report analyses the impacts that changes in trade structures, economic growth and technology have had on the greenhouse gas emissions (GhG) generated in the continent. It sets out climate change adaptation and mitigation strategies in the context of Africa's economic transformation and development. In this sense, it aims to identify the intersection between trade and climate policies and critical outcomes: the low-carbon and resilient economic development of the continent. Trade is an underlying driver of GhG emissions globally. GhG emissions from trade depend on energy efficiency via the technique effect and on GhG intensity of production via the composition effect, the two effects being compounded by the scale effect. Each effect is underpinned by emissions linked to international freight transport.
Keywords: 330; Agriculture & food; Climate finance; Africa; Climate change; Trade & investment